From Lecture Halls to Corporate Walls Bridging the Gap with Leap Forward - Choudhary, Devanshi (ATLAS SkillTech University, 2025)
Colgate-Palmolive is one of the largest and most competitive global consumer-goods areas: oral care, personal care, home care, and nutrition for pets. As a $9.4 billion company, it reaches consumers in over two hundred countries and territories, supplying health-related merchandise. Colgate-Palmolive's strategy is main brand building in its core segments of Oral Care, Personal Care, Household Surface Care, Fabric Care, and Pet Nutrition. Such core strengths of the company have allowed Colgate-Palmolive to achieve significant global growth as the firm continues to lead the products market in toothpaste, toothbrushes, soaps, deodorants, dishwashing detergents, household cleaners, fabric conditioners, and specialty pet food. This is because the commitment of the firm is to innovativeness combined with quality and appropriate brand reputation which is strong.
Project Report on From Lecture Halls to Corporate Walls Bridging the Gap with Leap Forward (2023-2025) Under the Guidance of Prof. Kajal Chheda
Keywords: competitive global consumer-goods; Household Surface Care; Personal Care; Fabric Care; Pet Nutrition; specialty pet food